The Effect of Permainan Galah Asin with Parental Support on Gross Motor Development in Mentally Disabled Students - Darta Pardamean Saragih; Suprayitno Suprayitno; Tarsyad Nugraha (Journal Physical Education, Health and Recreation, 2020)
This study aims to determine the effect of galah asin games with parental support on gross motor development at mentally disabled students. The population are students in the SMP SLB-E Negeri Pembina Utara in 2020, totaling 28 people. The instrument used in this study was a parent support instrument and also an instrument for basic movement skills, namely TGMD-2. The first analisys results of hypothesis show that modifikasi permainan galah asin has a better effect than the permainan galah asin on gross motor development in junior high school mentally disabled students at SLB-E Negeri Pembina Sumatera Utara. The second hypothesis is that there is an interaction between permainan galah asin with parental support for on gross motor development in junior high school mentally disabled students at SLB-E Negeri Pembina Sumatera Utara. The third hypothesis is that students with high parental support have a better influence than students with low parental support on on gross motor development in junior high school mentally disabled students at SLB-E Negeri Pembina Sumatera Utara. The fourth hypothesis is that the modifikasi permainan galah asin has a better effect than the permainan galah asin on gross motor development with high parental support at in junior high school mentally disabled students at SLB-E Negeri Pembina Sumatera Utara. The results of this study suggest that to develop gross motor development for mentally disabled students provide modifikasi permainan galah asin and the need for high parental support to assist children in carrying out every movement activity so as to get maximum benefits.